YAP1 Inhibition in HUVECs Is Associated with Released Exosomes and Increased Hepatocarcinoma Invasion and Metastasis - Yan Li; Xiaodong Zhang; Qianqian Zheng; Yijun Zhang; Yingbo Ma; Chen Zhu; Liang Yang; Xueqiang Peng; Qi Wang; Biao Wang; Xin Meng; Hangyu Li; et al. (Elsevier, 2020)
Hepatocellular carcinoma is one of the most common gastrointestinal malignancies. Anti-angiogenesis therapies have recently demonstrated promise in the treatment of malignancies, although early treatment benefits may be accompanied by metastasis over time. Additional and more effective anti-angiogenic treatment modalities are therefore needed. We previously found that Yes-associated protein 1 (YAP1) expression is increased in hepatocellular carcinoma (HCC), particularly around tumor-associated blood vessels, suggesting a role in angiogenesis. The YAP1 inhibitor verteporfin is presently in anti-angiogenic clinical trials for the treatment of various cancers. Depleted YAP1 from vascular endothelial cells effectively reduced proliferation and tube formation, validating its utility as an anti-angiogenesis target. We also showed that YAP1 depletion or inhibition in vascular endothelial cells leads to increased release of exosomes containing the long non-coding RNA (lncRNA) MALAT1 into the tumor microenvironment. Direct exosomal transfer of MALAT1 to hepatic cells leads to increased hepatic cell invasion and migration via activation of extracellular signal-regulated kinase 1/2 (ERK1/2) signaling. These observations may explain the occurrence of distant tumor metastasis with YAP1-associated anti-angiogenic therapy over time. It provides insight into new pathways and treatment paradigms that may be targeted to increase the long-term success of anti-angiogenic therapies.